(untitled) (Journal of the College of Basic Education, 2023)
The psychological problems left its effects in all spheres of life and in different age and academic stages of including adolescence , which left its impact on the future of the individual, especially the educational phase , which determine the future of the student academically and professionally as it is one of the smallest stages experienced by man in his life, and that justifies the study of problems The disadvantage faced by students who are mentally superior is that the current rapid changes in the current situation of the Iraqi society may create psychological pressures that affect the behavior of the individual negatively and that psychological problems represent a danger to the health and balance of the individual تهدد كيانه النفسي وماينشأ عنه من اثار سلبية على الصحة الجسمية والنفسية و اهمية الطلبة المتفوقين عقليا باعتبارهم ثروة الامة وقادة المستقبل لمساعدتهم في التعرف على مشاكلهم التربوية والنفسية والاجتماعية التي قد يتعرضون لها 0 ، وقد رأى الباحث بأن هذه المشكلة تستحق الاهتمام والدراسة العلمية ، وقد هدفت الدراسة الحالية الى بناء مقياس المشكلات النفسية لدى ال طلبة المتفوقين عقليا , وتعرف مستوى الفروق في ا المشكلات النفسية Threatening the psychological entity and Mainho him from the negative effects on the physical and mental health and the importance of outstanding students mentally as the nation ’s wealth and future leaders to help them identify the educational, psychological and social problems that may be exposed 0, saw the researcher that this problem deserves attention and scientific study . The study aimed current to build a measure of psychological problems among the outstanding students mentally, and know the differences in the level of psychological problems وفقا للجنس والمرحلة , وقد قام الباحث ببناء (أداة) مقياس المشكلات النفسية لدى ال طلبة المتفوقين عقليا , والذي تكون بصيغته النهائية من( 36 ) فقرة , بعد أن تم أستخراج صدق وتمييز الفقرات ومن ثم أستخراج صدق وثبات المقياس بأستخدام الوسائل الأحصائية المختلفة ، According to the sex stage, the researcher has built a (tool) psychological problems among the outstanding students mentally scale, which will be in its final form (36) paragraph, having been extracted sincerity and distinction paragraphs and then extract the validity and reliability of the scale using different statistical methods, بعد أن طبق المقياس على عينة التحليل الأحصائي البالغة (400) طالبا وطالبة والتي أختيرت بالأسلوب العشوائي من المدارس الثانوية للمتميزين ، وكذلك طبق المقياس على عينة الثبات البالغة ( 90 ) طالبا وطالبة , After the scale was applied to the sample of statistical analysis of (200) students, which was selected by the random method of secondary schools for distinguished , as well as applied the scale to the sample stability of ( 90 ) students, وطبق المقياس بصيغته النهائية على عينة التطبيق النهائي البالغة (200) The final measure was applied to the final application sample of (200) طالب وطالبة, وقد توصلت الدراسة الى أن مستوى المشكلات النفسية لدى الطلبة المتفوقين عقليا بشكل عام أعلى من المتوسط ، مع وجود فروق ذات دلالة أحصائية بين متغيري الجنس ولصالح عينة الذكور، ووجود فروق ذات Students, the study found that the level of psychological problems among students excelling mentally generally higher than average, with a statistically significant difference between the two variables of sex and in favor of the male sample, and the existence of differences with differences دلالة احصائية ولصالح Statistical indication and favor عينة الصف السادس ، وقد أوصت الدراسة بأدخال ال طلبة برامج أرشادية حول مواجهة ضغوطات الحياة الأجتماعية والأقتصادية ,مع أمكانية أجراء دراسة مماثلة على الطلبة في المدارس الاعتيادية ومقارنة نتائجها مع نتائج الدراسة الحالية Sample sixth grade, the study had recommended the students of outreach programs on the face of the pressures of social and economic life, with the possibility of conducting a similar study on students in regular schools and compared their results with the results of the current study . .